The Effect of Jumbled Letters Game on Vocabulary Mastery of Seventh Grade Students At Smpn 11 Mataram - Anggrianingsih; Thohir, Lalu; Baharuddin; Amrullah (Journal of Classroom Action Research, 2025)
This study aims to determine the effect of using the jumbled letters on the vocabulary mastery of seventh-grade students at SMPN 11 Mataram. This research was pre-experimental research with a one-group pre-test post-test design. The population in this study was all seventh-grade students at SMPN 11 Mataram and used a purposive sampling, which included 24 students from VII A. Data collection was divided into three stages, namely pre-test, treatment, and post-test. Data were analyzed using paired sample t-test SPSS version 27. The result obtained from the data analysis showed that the average pre-test value was 57.2917, and after treatment, the average post-test value increased to 88.3333. A paired sample t-test was used to test the hypothesis and showed a significance value of 0.00. The significance value was lower than the alpha value of 0.05. This means that Ho is rejected and Ha is accepted. The use of jumbled letters is very effective in teaching vocabulary to students and can effectively improve students’ vocabulary mastery.